1997
DOI: 10.1002/hep.510250412
|View full text |Cite
|
Sign up to set email alerts
|

Expression of urokinase-type plasminogen activator receptor in hepatocellular carcinoma

Abstract: hepatic metastasis in their resected liver have shown recurIt is well known that a urokinase-type plasminogen rence within 3 years, 9 prompting us to seek a new predictor activator receptor (uPAR) is a key protein in the plasfor this recurrence. minogen activation system, which plays a proteolyti-The metastatic process in malignant tumors involves local cally important role in the invasion and metastasis of invasion, intravasation, and extravasation. 10 These events various cancer cells. To assess the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
(16 reference statements)
4
31
0
1
Order By: Relevance
“…u-PAR has also been documented in hepatocellular carcinoma (8,9,12). Our present study using immunohistochemical and western blot techniques corroborates the previous work.…”
Section: U-pa/plasmin and Hgfasupporting
confidence: 92%
“…u-PAR has also been documented in hepatocellular carcinoma (8,9,12). Our present study using immunohistochemical and western blot techniques corroborates the previous work.…”
Section: U-pa/plasmin and Hgfasupporting
confidence: 92%
“…The chief components of GSG are heparan sulfate proteoglycans (HSPGs) that are principally composed of a core protein covalently linked to several heparan sulfate side chains [1] . Over the past ten years, most studies about neoplasm metastasis including HCC, focused on some proteases, such as matrix metalloproteinases (MMPs) [2][3][4] , u-PA [5,6] , serine and cysteine protease [7,8] whose substrates were structural proteins, but heparanase (HPA), whose substrate was GSGs, was ignored. In recent years, mammalian HPA gene has successfully been cloned and sequenced in Israel and U.S.A [9][10][11][12][13] , and HPA was found to play an important role in tumor invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) On the other hand, PAI-1 suppresses metastasis in murine models of prostate carcinoma and melanoma. 16,17) We have reported that the plasminogen activation system is positively related to the invasion and postoperative recurrence of hepatocellular carcinoma (HCC), 18) suggesting that the inhibition of uPA-mediated proteolysis may contribute to the inhibition of HCC progression.…”
mentioning
confidence: 99%